Network analysis and Canada's large value transfer system - Lana Embree; Tom Roberts (Bank of Canada, 2009)
Analysis of the characteristics and structure of a network of financial institutions can provide insight into the complex relationships and interdependencies that exist in a payment, clearing, and settlement system (PCSS), and allow an intuitive understanding of the PCSS's efficiency, stability, and resiliency. The authors review the literature related to the PCSS network and describe the daily and intraday network structure of payment activity in the Large Value Transfer System (LVTS), which is an integral component of Canada's financial system. The picture that emerges confirms that the LVTS is highly centralized among a few key participants, similar to other PCSSs, based on the network of relationships. This could heighten the systemic importance of these participants, and the susceptibility of the system to financial contagion. There have been small variations in the relative importance of individual banks, but the network-wide pattern of relationships has remained stable from 2004 to 2008, even through the credit crisis.
Keywords: D85; G10; 330; Payment; clearing; and settlement systems; Financial stability; Zahlungsverkehr; Verrechnungsverkehr; Bankensystem; Kanada